2016
DOI: 10.1024/1421-0185/a000182
|View full text |Cite
|
Sign up to set email alerts
|

Positivity and Negativity in Interparental Conflict

Abstract: Although children are known to be highly sensitive to interparental conflict, important questions remain regarding which specific combinations of positive and negative behaviors as well as verbal and nonverbal expressions are most predictive of children's perceptions. In this pilot study, we examined observational data on interparental conflict as predictors of children's reports of perceived threat and insecurity in 43 families. Fathers' nonverbal negativity was strongly linked to children's perceived threat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Specifically, a lower relationship quality can be characterized by more negativity in the relationship (i.e., higher levels of interparental conflict), but also by less positivity (i.e., lower relationship satisfaction). Thus, we decided to include these two constructs as our target variable (Zemp, Bodenmann, Backes, Sutter-Stickel, & Bradbury, 2016). The second objective is to investigate whether any of the factors discussed above, namely age and gender of the child, the comorbidity with either ODD or CD, and the source of the relationship rating, moderate the strength of the mean difference (Cohen’s d ) in parental relationship quality between families of children with ADHD versus healthy children.…”
Section: The Current Meta-analysismentioning
confidence: 99%
“…Specifically, a lower relationship quality can be characterized by more negativity in the relationship (i.e., higher levels of interparental conflict), but also by less positivity (i.e., lower relationship satisfaction). Thus, we decided to include these two constructs as our target variable (Zemp, Bodenmann, Backes, Sutter-Stickel, & Bradbury, 2016). The second objective is to investigate whether any of the factors discussed above, namely age and gender of the child, the comorbidity with either ODD or CD, and the source of the relationship rating, moderate the strength of the mean difference (Cohen’s d ) in parental relationship quality between families of children with ADHD versus healthy children.…”
Section: The Current Meta-analysismentioning
confidence: 99%
“…These steps were repeated for the coding of the second partner. This coding method demonstrated good validity in previous studies (Kuster et al, 2015;Zemp et al, 2016Zemp et al, , 2017, and rater teams achieved a high interrater reliability (i.e., Cohen's kappa ≥ 0.90) in previous research (Zemp et al, 2017;Leuchtmann et al, 2019). A master coder from the University of Zurich trained the first author.…”
Section: Affective Behaviormentioning
confidence: 85%
“…The SPAFF has been widely used and is an attested and externally validated approach to the coding of observational data, particularly for affective behavior in couples ( Johnson, 2002 ; Zemp et al, 2017 ). This adapted system allowed the coding of discrete behaviors and is comprised of observational scales divided in five main categories: nonverbal positivity, nonverbal negativity, verbal positivity, verbal negativity, and neutral/nothing ( Zemp et al, 2016 ). The verbal positivity category is composed of five subcategories: interest, validation, affect/caring, emotional disclosure, and constructive criticism.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This line of experimental research has revealed two important findings: First, children's responses to experimental conflict vary depending on the specific form of conflict expression that is displayed. Conflict resolution emerged as a critical dimension to determine how children perceive and react to couple interactions (Zemp, Bodenmann, Backes et al, 2016). Analog studies reported that unresolved conflict stimuli elicited more distress and more negative appraisals in children than resolved conflicts or neutral conversations (Goeke‐Morey et al, 2007; Shifflett‐Simpson & Cummings, 1996).…”
Section: Impact Of Interparental Conflict On Children's Cognitive Funmentioning
confidence: 99%